Analysis of tool vibration and surface roughness during turning process of tempered steel samples using Taguchi method. (October 2021) - Kam, Menderes; Demirtaş, Mustafa
This study analyzed the tool vibration (Vib) and surface roughness (Ra) during turning of AISI 4340 (34CrNiMo6) tempered steel samples using Taguchi Method. In this context, Taguchi design L18 (2 1 × 3 2 ) was used to analyze the experimental results. The vibration amplitude values from cutting tools were recorded for different machining parameters, control factors; two different sample hardness (46 and 53 HRc), three different cutting speeds (180, 220, 260 m.min −1 ), and feed rates (0.08, 0.14, 0.20 mm.rev −1 ) were selected. The machining parameters giving optimum Vib and Ra values were determined. Regression analysis is applied to predict values of Vib and Ra. Analysis of variance was used to determine the effects of machining parameters on the Vib and Ra values. The most important machining parameters were found to be the feed rate, sample hardness, and cutting speed for Vib and Ra, respectively. The lowest Vib and Ra values were obtained in 46 HRc sample as 0.0022 gRMS and 0.255 µm, respectively. The surface quality can be improved by reducing the sources of vibration by using appropriate machining parameters. As a result, there is a significant relationship between Ra and Vib. The lower Ra values were found during turning process of tempered steel samples according to the literature studies. It is suggested that the process can be preferred as an alternative process to grinding process due to lower cost and machining time. In application of the turning of experiment samples by ceramic cutting tool, a substantial technological and economical benefit has been observed.